Expenditure analysis of the farm household economy in Malay paddy growing villages. - Terano, Rika; Mohamed, Zainalabidin (2012)
Malaysia has experienced tremendous economic transformation from agriculture based to a manufacturing based. Such development has spillover effect on the livelihood of farming household in paddy growing areas by engaging in the off-farm income activities. Household income level in Malaysia has improved, which gave a great change on people’s life-style with improvement of living standard. However, there have been income inequalities between the East and West Coast of Peninsular Malaysia paddy area due to the locational difference of industrial parks, where most of the industrial parks are located in the West Coast. The east coast farming areas might have experienced different phase of transformation in living standard compare to the West Coast people in the vicinity of industrial parks. In the midst of socio-economic changes in the paddy farming sector, it is necessary to clarify the living standard and life-style among the East Coast people vis a vis to the west coast paddy farming community of Peninsular Malaysia. This study aims to examine patterns of household expenditure in relations to household income. We identified actual expenses and detailed consumption items for basic subsistence at the household level in four paddy farming areas. A structured questionnaire was designed to capture the information needed and surveys were conducted in four rice granary areas in the states of Penang and Kedah in the West Coast and Terengganu and Kelantan in the East Coasts. The food expenditure and electricity bill were two of main expenditure items in the four areas. The results indicate that on average the household expenditure in east coast is lower compare to the West Coast with an Engel’s coefficient at 43.3%. While in the East Coast areas, on average the Engle’s coefficient is about 33.6%. The expenditure function indicates that off-farm income and number of family members are the major determinants influencing the expenditure level.